Do Gratitude and Social Support Influence Hijrah Woman’s Well-being? - Liany Luzvinda; Abdul Rahman Saleh (‎‎‎TAZKIYA Journal of Psychology, 2020)
Nowadays the fenomenon of emigrate (Hijrah) becoming a trend in Indonesia. Hijrah means to change ourselves for the better, in accordance with the religion guidance. Deciding to change and get out of  the comfort zone it is not an easy task. Individual who try to emigrate often feel doubts, feel lonely due to being left behind by friends, facing cornering questions and comments. This research was conducted to find out the well-being emigrate women caused by gratitude and social support, using 200 young mothers who decided to Hijrah. The questionnaires for measuring subjective well-being using Flourishing Scale by Diener, Oishi, et al., (2009) and SPANE (Scale of Positive and Negative Experience) by Diener, Wirtz, et al., (2009), gratitude using GRAT (The Gratitude Resentment and Appreciation Test) by Watkins et al., (2003), and social support using MSPSS (Multidimensional Scale of Perceived Social Support) by Dahlem et al., (1991). Confirmatory Factor Analysis (CFA) was used to test the validity of each item in the questionnaire. Data analysis technique used in this study is multiple regression analysis (multiple regression analysis) of SPSS for windows. In this study we hypothesized that there would be significant influence of gratitude and social support on emigrate woman. Our result shows that, only sense of abundance has a significant effect to well-being of woman who emigrate but there is no social support that has  a significant effect to well being on them.